Analisis Akad dan Perlindungan Konsumen Dalam Uang Elektronik - Dwinugrah Yogas Sukmaya; Rahmawati Firanti Nur; Febri Adhi Anggoro; Alfiyan Nur Rohman; Waluyo Waluyo (Indonesian Journal Publisher, 2025)
This study aims to analyze contracts (akad) and consumer protection in the use of electronic money in Indonesia, with a focus on the application of Islamic economic principles. The research employs a qualitative method with a literature study approach, enabling the collection and analysis of information related to fintech innovations, particularly digital wallets such as GoPay, OVO, and Dana, as well as the QRIS payment system implemented by Bank Indonesia. The findings indicate that a proper understanding of the types of contracts applied, such as deposit (wadi’ah) or loan (qardh), is crucial to ensure compliance with Sharia values. In addition, this study identifies risks and challenges faced by consumers, including data protection and potential misuse. The conclusion highlights the need for strong regulations and strict security systems to safeguard consumers, as well as the importance of public education regarding contracts and risks associated with electronic money. Furthermore, innovations in Sharia-based services are necessary to establish a more equitable and sustainable financial ecosystem, thereby enhancing public trust in the use of electronic money.